2013
DOI: 10.1371/journal.pone.0056969
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasma PFOA and PFOS Levels and Total Cholesterol in a Middle-Aged Danish Population

Abstract: Perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) are used in a variety of consumer products and have been detected worldwide in human blood. Recent studies mainly of highly exposed populations have indicated that PFOA and PFOS may affect serum cholesterol levels, but the magnitude of the effect may be inconsistent across exposure levels. The aim of the present cross-sectional study was to investigate the association between plasma PFOA and PFOS and total cholesterol in a general, middle-aged Dani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 26 publications
5
100
0
4
Order By: Relevance
“…In terms of magnitude the associations between both PFOS and PFOA with total serum cholesterol was comparable to that observed for high saturated fat intake during pregnancy. The positive association observed between serum concentrations of PFOS and PFOA with total cholesterol in our study is in line with what has previously been reported among the general public (Eriksen et al, 2013;Nelson et al, 2010), in highly exposed populations (Costa et al, 2009;Frisbee et al, 2010;Olsen et al, 2003;Sakr et al, 2007aSakr et al, , 2007bSteenland et al, 2009), and in pregnant women (Jain, 2013;Starling et al, 2014). The strength of the associations reported in these studies has, however, varied considerably.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of magnitude the associations between both PFOS and PFOA with total serum cholesterol was comparable to that observed for high saturated fat intake during pregnancy. The positive association observed between serum concentrations of PFOS and PFOA with total cholesterol in our study is in line with what has previously been reported among the general public (Eriksen et al, 2013;Nelson et al, 2010), in highly exposed populations (Costa et al, 2009;Frisbee et al, 2010;Olsen et al, 2003;Sakr et al, 2007aSakr et al, , 2007bSteenland et al, 2009), and in pregnant women (Jain, 2013;Starling et al, 2014). The strength of the associations reported in these studies has, however, varied considerably.…”
Section: Discussionsupporting
confidence: 92%
“…These studies include both occupationally exposed workers, subjects from communities with high exposure levels (Costa et al, 2009;Frisbee et al, 2010;Olsen et al, 2003;Sakr et al, 2007aSakr et al, , 2007bSteenland et al, 2009) and the general population (Eriksen et al, 2013;Nelson et al, 2010) including pregnant women (Jain, 2013;Starling et al, 2014). However, several studies have reported no association (Emmett et al, 2006;Olsen et al, 2000Olsen et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning background populations, elevated serum PFOS, PFOA, PFNA levels have been associated positively (and PFHxS negatively) with elevated cholesterol [285,308]. Another study found, however, a positive association with PFHxS [309].…”
Section: General Populationmentioning
confidence: 95%
“…A transcriptional analysis that found changes in the expression of genes related to cholesterol metabolism and suggested that exposure to PFOA may promote a hypercholesterolemic environment [283] was criticized and deemed unsubstantiated [284]. Decrease of LDL cholesterol with decrease in serum PFOA after exposure to contaminated drinking water was ended, indicated a causal relation [285].…”
Section: More Exposed Populationsmentioning
confidence: 99%